Correlação entre a dilatação fluxo mediada (FMD) da artéria braquial e os valores séricos maternos de PLGF e sFlt-1 em gestantes normais e complicadas por pré-eclampsia - Cristina Marcia Nogueira Salomao (2011)
Introduction: preeclampsia (PE) is a relevant obstetric disease, which causes high maternal and fetal morbidity, and has been considered the main cause of perinatal mortality, prematurity and intra uterine growth restriction, especially in developing countries. The endothelial lesion is currently considered the central point and unquestionable in the pathophisiology of this disease, and is being studied in the fetal medicine center of the Federal University of Minas Gerais (UFMG). Several markers of endothelial damage have been found and correlated with the occurrence of preeclampsia. Currently, most studies on the prediction of preeclampsia are using biochemical and biophysical methods. Objectives: This study aims to compare the biochemical markers of endothelial lesion PLGF and sFlt-1 and the biophysical marker FMD (flow mediated dilatation) of brachial artery in normal pregnancies and in pregnancies complicated with preeclampsia as well as whether there is a correlation between these markers. Patients and Methods: this is a cross-sectional study that evaluated 80 pregnant women at the maternity of the University Hospital from Minas Gerais, 52 of them with diagnosis of preeclampsia (NHBPEPWG, 2000) and 28 normotensive. The patients underwent ultrasound studies for the calculation of the flow mediated dilatation according to the technique described by Anderson and Mark (1989), as adapted. This was followed by collection of blood samples to determine the plasmatic of PLGF and sFlt-1 (ELISA assay). The gestational age of the group ranged between 20 and 41 weeks of gestation. Results: there was a significant reduction of FMD (p 0,000) and significant increase of the concentration of sFlt-1(p 0,001) and the sFlt-1/PLGF index (p 0,041) in patients with preeclampsia compared to normotensive group; however, there was no difference between the concentration of PLGF in both groups (p 0,274). No correlation was found between any of the markers studied. Conclusion: although the biophysical marker FMD and the biochemical marker sFlt- 1 not correlate with each other, they have statistically different behavior between the patients with preeclampsia and normotensive pregnant women.